ASITA'S IN MANAGEMENT OF TRAVEL AGENCY IN SOUTHERN TANGERANG AS CULTURAL TOURISM BUSINESS OPPORTUNITIES IN THE ERA OF DIGITALISATION - Sakti Brata Ismaya; Ani Nuraini; Titus Indrajaya; Sri Yulianti; Eros Rosmiati; Hammad Bawazir; Ignatius Erik Sapta Yanuar (Yayasan Education and Social Center, 2022)
Many travel agency business owners face a tourism industry crisis that has not improved in the last two decades due to the effects of the covid 19 outbreak, which has been the focus of community service efforts in recent years. The South Tangerang ASITA community, in conjunction with the South Tangerang City Tourism Office (Dispar), recently hosted a Travel Agency (BPW) Training and deliberations on the Tangerang Association of The Indonesia Tour & Travel Agencies (ASITA) branch as part of efforts to revitalise the city's tourism industry during the current endemic period. Southern Tangerang also cooperates with Universitas Respati Indonesia and LSP WHI. This training event proves that ASITA South Tangerang is ready to exist again as an entry point for Banten tourism and alternative tourism for residents and foreign tourists. As a result, ASITA is reaching out to travel agents to explore online travel business opportunities in this age of rapid digitalisation together. South Tangerang's tourist attractions are evidence of the region's appeal to domestic and international travellers; seizing this opportunity, ASITA members have relaunched their tour and travel agency. South Tangerang City's tourism industry players need to get creative in the face of digital disruption if they want to grow their enterprises and thrive in the emerging market conditions. Tourism marketing management has undergone significant transformations to adapt to the digital age. South Tangerang City's government, hotels, gastronomic SMEs, the Creative Economy, and ancillary service providers are all working together to boost the quality of their human resources in the tourism sector. Then, employ digital tourism for more proactive advertising and to maintain infrastructure on access to tourist destinations and communities near tourist destinations